Recent Insights into the Management of Inflammation in Asthma - Rupani H; Fong WCG; Kyyaly A; Kurukulaaratchy RJ (Dove Medical Press, 2021)
Hitasha Rupani,1 Wei Chern Gavin Fong,2,3 Aref Kyyaly,2,3 Ramesh J Kurukulaaratchy1- 4 1Department of Respiratory Medicine, University Hospitals Southampton NHS Foundation Trust, Southampton, UK; 2Clinical and Experimental Sciences, University of Southampton, Southampton, UK; 3David Hide Asthma and Allergy Research Centre, Isle of Wight NHS Trust, Isle of Wight, UK; 4NIHR Biomedical Research Centre, University Hospitals Southampton NHS Foundation Trust, Southampton, UKCorrespondence: Ramesh J KurukulaaratchyClinical Experimental Sciences, University of Southampton, Southampton, UKTel +44 238120 5232Email R.J.Kurukulaaratchy@soton.ac.ukWei Chern Gavin FongClinical and Experimental Sciences, University of Southampton, Southampton, UKTel +44 2381205232Email W.C.Fong@soton.ac.ukAbstract: The present prevailing inflammatory paradigm in asthma is of T2-high inflammation orchestrated by key inflammatory cells like Type 2 helper lymphocytes, innate lymphoid cells group 2 and associated cytokines. Eosinophils are key components of this T2 inflammatory pathway and have become key therapeutic targets. Real-world evidence on the predominant T2-high nature of severe asthma is emerging. Various inflammatory biomarkers have been adopted in clinical practice to aid asthma characterization including airway measures such as bronchoscopic biopsy and lavage, induced sputum analysis, and fractional exhaled nitric oxide. Blood measures like eosinophil counts have also gained widespread usage and multicomponent algorithms combining different parameters are now appearing. There is also growing interest in potential future biomarkers including exhaled volatile organic compounds, micro RNAs and urinary biomarkers. Additionally, there is a growing realisation that asthma is a heterogeneous state with numerous phenotypes and associated treatable traits. These may show particular inflammatory patterns and merit-specific management approaches that could improve asthma patient outcomes. Inhaled corticosteroids (ICS) remain the mainstay of asthma management but their use earlier in the course of disease is being advocated. Recent evidence suggests potential roles for ICS in combination with long-acting beta-agonists (LABA) for as needed use in mild asthma whilst maintenance and reliever therapy regimes have gained widespread acceptance. Other anti-inflammatory strategies including ultra-fine particle ICS, leukotriene receptor antagonists and macrolide antibiotics may show efficacy in particular phenotypes too. Monoclonal antibody biologic therapies have recently entered clinical practice with significant impacts on asthma outcomes. Understanding of the efficacy and use of those agents is becoming clearer with a growing body of real-world evidence as is their potential applicability to other treatable comorbid traits. In conclusion, the evolving understanding of T2 driven inflammation alongside a treatable traits disease model is enhancing therapeutic approaches to address inflammation in asthma.Keywords: asthma, biologics, monitoring, respiratory disease, T2 inflammation, treatable traits